APPROACHES TO CLASSIFICATION OF E-COMMERCE SYSTEMS INFRASTRUCTURE - Baran, R.Yа. (The actual problems of regional economy development, 2018)
The article focuses on the research of the components of e-commerce systems and their systematization. The objective of the article lies in researching the specifics of the key instruments and tools for supporting the systems of e-commerce, as well as in improving the existing classifications of its infrastructure. The article analyzes the existing approaches to the classification of the elements of e-commerce systems infrastructure, thus enabling to determine their major advantages and disadvantages. It offers an approach that allows for examining the infrastructure of e-commerce systems at seven different levels: IT infrastructure, telecommunication infrastructure, organizational and legal infrastructure, financial infrastructure, logistic infrastructure, marketing infrastructure and personnel infrastructure.